2014
DOI: 10.1080/10941665.2014.925482
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nature-based Tourism, Destination Attachment and Property Ownership on Environmental-friendliness of Visitors: A Study in Thailand

Abstract: This study examines whether international visitors' pro-environment attitudes is enhanced by the experience of nature-based tourism, destination attachment and ownership of property at the destination. It also examines whether visitors are obstructed from exhibiting pro-environment attitudes and behaviors by situational barriers at the destination. A questionnaire survey was employed to test the hypotheses. The main sample of 300 respondents was collected in Thailand in two main tourism regions. Results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 45 publications
4
41
0
1
Order By: Relevance
“…The results are in line with the research put forward by researchers who discussed the importance of community participation in the development of CBT (Li & Hunter, 2015); (Stone, 2015); (Giampiccoli & Mtapuri, 2015); (Towner & Towner, 2016); (Park et al, 2017); (Kunjuraman & Hussin, 2017); (Mayaka et al, 2017). The survey results also support researchers who state that ownership is a determining factor for the successful management of CBT (Chubchuwong et al, 2015); (Hampton & Jeyacheya, 2015); (Jones, Diggle, & Thouless, 2015); (Dolezal & Burns, 2015). These three dimensions are perceived almost the same by all respondents, which is above 90%.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results are in line with the research put forward by researchers who discussed the importance of community participation in the development of CBT (Li & Hunter, 2015); (Stone, 2015); (Giampiccoli & Mtapuri, 2015); (Towner & Towner, 2016); (Park et al, 2017); (Kunjuraman & Hussin, 2017); (Mayaka et al, 2017). The survey results also support researchers who state that ownership is a determining factor for the successful management of CBT (Chubchuwong et al, 2015); (Hampton & Jeyacheya, 2015); (Jones, Diggle, & Thouless, 2015); (Dolezal & Burns, 2015). These three dimensions are perceived almost the same by all respondents, which is above 90%.…”
Section: Resultssupporting
confidence: 88%
“…But ownership alone is not enough, transfer of ownership from an external actor to the community will only be successful if the community has the required management skills necessary to run the project as a commercial business (Rodrigues & Prideaux, 2017). Basically, ownership of the property at the destination enhances their sense of attachment to the destination (Chubchuwong, Beise-zee, & Speece, 2015).…”
mentioning
confidence: 99%
“…Research under the latter topic focuses on examining the environmentally-sustainable behaviour that tourists exhibit while travelling. Several models have been proposed to fulfil this goal [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the concepts of regional identity or place attachment can play an important role in environmental behaviour [14,15]. Tourists are different from normal local residents because of their temporary status as visitors to a destination [6]. Hence, Kollmuss and Agyeman [16] indicated that the relationship between environmental attitudes and environmentally-friendly behaviour is expected to be weaker when the cost of not acting pro-environmentally is relatively low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation